2018
DOI: 10.1002/joc.5820
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of climate model biases to biophysical modelling can complicate assessments of climate change impact in agricultural systems

Abstract: Regional climate model (RCM) simulations are being increasingly used for climate change impact assessments, but their application is challenging due to considerable biases inherited from global climate model (GCM) simulations and generated from dynamical downscaling processes. This study assesses the biases in NARCliM (NSW and ACT regional climate modelling) simulations and quantifies the consequence of the climate biases in the downstream assessment of climate change impact on wheat crop system, using the Agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The contribution of the biases in gridded climate variables to the biases in biophysical modelled outputs was quantified by the regression coefficients in Table . The different MBEs of climate variables had different effects on the MBEs in modelled outputs because different functionalities of climate variables were implemented in the biophysical model (Liu et al ., ). Regression analysis showed that the MBE in climate variables could account for an average of 71–92% (R 2 : .71 ± .20 ~ .92 ± .06) of the variance in the MBEs for APSIM‐simulated phenological parameters.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The contribution of the biases in gridded climate variables to the biases in biophysical modelled outputs was quantified by the regression coefficients in Table . The different MBEs of climate variables had different effects on the MBEs in modelled outputs because different functionalities of climate variables were implemented in the biophysical model (Liu et al ., ). Regression analysis showed that the MBE in climate variables could account for an average of 71–92% (R 2 : .71 ± .20 ~ .92 ± .06) of the variance in the MBEs for APSIM‐simulated phenological parameters.…”
Section: Resultsmentioning
confidence: 99%
“…This could result in misrepresentation of production in spatial analyses including climate change impact assessments. This finding is similar to climate biases from other sources such as dynamical downscaling (Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations